How Apolitical Were Epicure and the Epicureans?: The Greek Polis and Their Illustrious Epicurean Citizens [¿Cuán Apolíticos Fueron Epicuro y Los Epicúreos? la Polis Griega y Sus Ilustres Ciudadanos Epicúreos] - Aoiz-Monreal, F (Universidade Estadual Paulista (UNESP), 2022)
In this paper, we argue that the fact that there were prominent citizens of different Greek cities who adhered to Epicureanism, felt themselves Epicurean, and were recognized as such, shows that slogans such as “live unnoticed” and “do not participate in politics” (which suggest a complete apoliticism on Epicurus’ and the Epicureans’ part) misrepresent the true meaning of the Epicurean staying away from contingent politics. Our article shows the interaction between Epicurus and the Epicureans and the Greek cities through the analysis of documents (some of them, well known –such as Epicurus’ Testament, which shows the connections of the philosopher with the political life of the city–, others less known of epigraphic character) related to different ancient cities. If what we argue is sound, the usual idea that Epicureanism recommends apoliticism must be discarded. © 2022, Universidade Estadual Paulista (UNESP). All rights reserved.